Estrategias de aprendizaje y logro de capacidades en estudiantes del área de ciencias sociales en la institución educativa Miguel Acosta Oyarce, Caballococha 2024 - Garcia Barbaran, Rocio del Pilar (2025)
Inquiry in order to determine the relationship between learning strategies and achievement of abilities in students in the area of Social Sciences at the Educational Institution “Miguel Acosta Oyarce” Caballococha 2024. This study uses a non experimental quantitative approach of a descriptive - correlational type, with a descriptive design. cross. With a population of 166 students and a sample of 117 students from the 2nd year of secondary school sections A, B C and D, of the “Miguel Acosta Oyarce” Caballococha Educational Institution, enrolled in the 2024 school year. The technique used in data collection was the interview and documentary analysis and as instruments, the questionnaire and the report cards. The data were processed using the statistical package SPSS (Statistical package for social sciences), edition 29 in Spanish and an Excel spreadsheet. The descriptive analysis, frequency, average, percentages, interpretation of the information and hypothesis testing, was carried out using the inferential statistical test Chi Square (X2) with α = 0.05% and confidence level of 0.95%, finding that X_c is true ^2>X_0.05^2 that is, 15.96079171 >12.59158724, proving that there is a relationship between the variables Learning Strategies and Skill Achievements. The hypothesis was accepted: there is a relationship between learning strategies and achievement of abilities in students in the area of Social Sciences at the Educational Institution “Miguel Acosta Oyarce” Caballococha 2024.